, : ; Forums, fees and data flows: Coordinating mining and water policy in Mongolia - Mirja Schoderer; Ines Dombrowsky (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
, . . . (), , . , , . , , . , . , . () - . . 2019 , . , . , , . . : * , * - ( - ) , , * * * - . – – This Briefing Paper presents one of six analyses of cross-sectoral coordination challenges that were conducted as part of the STEER research project and on which separate Briefing Papers are available. The extraction of minerals and metals comes with a large water footprint, both in terms of water needed for extraction itself and in terms of wastewater discharge and the potential pollution of water resources. Thus, coordination between the mining and water sectors is key. A number of instruments to that end have been devised, which aim to mitigate the negative impacts of mining on water resources and on water-resource dependent communities. Among these are environmental impact assessments (EIAs), stakeholder involvement within these processes and within river basin management, and payment schemes that incentivise wastewater treatment at the mine. Whether and how these instruments are implemented depends on the national, provincial and local context, since each instrument involves a number of preconditions. Assessing the effectiveness of these instruments thus requires a sound analysis of the governance system within which they operate. In this Briefing Paper, we focus on Mongolia as an example case study and look at stakeholder involvement and incentivising wastewater treatment as two key strategies to increase coordination. We assess how these strategies are translated into policies and how they are implemented on the ground in two adjacent river basins. In doing so, we pay particular attention to the human and financial capacities of lower-level administrative entities, as well as to the availability of water-related information, as essential prerequisites for effective natural resource governance. We find that the Mongolian governance system stipulates the implementation of stakeholder involvement through multiple processes, most importantly through River Basin Multi-Stakeholder Platforms (RB-MSPs) and community consultation within the EIA procedure. In practice, however, the RB-MSP in the study area has yet to diversify its membership from mostly lower-level administrative staff, and community consultations rarely take place. In terms of incentivising wastewater treatment, Mongolia passed amendments to its Water Pollution Fee Law in summer 2019 and is now working on implementation guidelines. Challenges here relate to the collection of data for a baseline on water quality and to guarantees for adequate sampling and analysis. This is tied to the limited human and financial capacity of lower-level administrative entities, which struggle to access or evaluate relevant data. We recommend that: * the diversity of stakeholders in RB-MSPs is increased to better include the private sector and civil society, with sensitivity to differences in socioeconomic standing to ensure equitable access to and deliberation within the platform; * the enacting of public consultations as part of EIAs is ensured and governmental procedures (i.e. mining licensing and approval of EIAs) are made more transparent and accountable; * public availability of water data is increased; * the Water Pollution Fee Law is implemented swiftly to provide incentives for the treatment of mining wastewater before discharge; * funding and institutional capacity development for lower-level administrative bodies are increased and funding for RB-MSPs is provided to enable them to fulfill their mandates.
Keywords: 330